The Rise of the Dutch Republic $1 (BVolume 20: 1573s - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rise of the Dutch Republic $1 (BVolume 20: 1573" by John Lothrop Motley is a historical account written in the mid-19th century. The book explores the events and pivotal moments during the late 16th century as the Dutch people rise in rebellion against Spanish rule, focusing specifically on the siege of Alkmaar and the actions of key figures like the Duke of Alva and the Prince of Orange. This work not only details military strategies and political maneuvers but also delves into the motivations behind the quest for independence in the context of religious freedom and national identity. In this volume, Motley recounts the trials faced by the besieged city of Alkmaar and the audacious defense mounted by its citizens against the Spanish forces led by Alva, who is portrayed as both a skilled military strategist and a cruel tyrant. The narrative describes the psychological toll that oppression has taken on the Dutch populace, highlighting their determination to fight for their freedom, even in the face of overwhelming odds. The story emphasizes the courage of the common people and the dynamic leadership of the Prince of Orange, who inspires hope and resilience. Ultimately, the siege of Alkmaar becomes a symbol of resistance, demonstrating how the spirit of rebellion can prevail against tyranny, and laying the groundwork for the eventual independence of the Dutch Republic. (This is an automatically generated summary.)s
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648; Netherlands -- Church history